PENGARUH PERATAAN LABA DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN RISIKO PASAR SEBAGAI VARIABEL MODERASI - Destria Melia Rahma; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2023)
The purpose of this research is to examine the effect of income smoothing and capital structure on firm value with market risk as a moderating variable. The population in this research are manufacturing companies subsector pharmacy listed on the Indonesia Stock Exchange (IDX) in 2014 – 2021. This research uses multiple regression analysis using the SPSS 26 program. The sample selection uses a purposive sampling method which produces 72 sample that are worth observing and researching. Based on the analysis results show that, income smoothing has a negative impact on firm value, capital structure has not a negative impact on firm value and market risk has not strengthes income smoothing on firm value and market risk. The result of this research have several practical and theoritical implications, companies must minimize the practice of income smoothing so that published financial reports reflect the actual condition of the company in order to increase the firm value along with investor confidence to invest.